2012
DOI: 10.1007/s12160-012-9405-2
|View full text |Cite
|
Sign up to set email alerts
|

The Alberta Diabetes and Physical Activity Trial (ADAPT):A Randomized Trial Evaluating Theory-Based Interventions to Increase Physical Activity in Adults with Type 2 Diabetes

Abstract: No significant effects were found for PA or A1c levels for T2DM adults. The multi-component strategy including telephone counseling may have potential for women. The trial was registered on ClinicalTrials.gov identifier: NCT00221234.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(93 citation statements)
references
References 43 publications
3
84
0
6
Order By: Relevance
“…Plotnikoff et al, (2013), however, found no significant improvement in the level of physical activity or hemoglobin A1c in T2DM patients using distance education with print-based materials alongside pedometer use and telephone counseling, although this intervention did increase the steps counts between women [34].…”
Section: Discussionmentioning
confidence: 98%
“…Plotnikoff et al, (2013), however, found no significant improvement in the level of physical activity or hemoglobin A1c in T2DM patients using distance education with print-based materials alongside pedometer use and telephone counseling, although this intervention did increase the steps counts between women [34].…”
Section: Discussionmentioning
confidence: 98%
“…No G2 a maioria (54,0%) era viúvo, e apenas 23,0%, casados. Estudos que investigaram o aconselhamento telefônico como ferramenta de intervenção para incrementar a prática de atividade física com pacientes com DM, mostraram predominância de pessoas casadas (EAKIN et al, 2010a;GOODE et al, 2011;PIETTE et al, 2011;PLOTNIKOFF et al, 2012. No presente estudo observou-se que a maioria dos familiares do G1 e G2 Quanto à ocupação, observou-se que a maioria dos pacientes é aposentado.…”
Section: Caracterização Dos Pacientes Com Diabetes Mellitus Segundo Aunclassified
“…No Brasil, verificou-se que não há estudos que permitem a comparação dessa variável utilizando o suporte telefônico como estratégia educativa. Em relação aos estudos internacionais, a classificação utilizada da variável escolaridade pelos autores de três estudos que investigaram o suporte telefônico como estratégia educativa, não permite comparação com os dados do presente estudo (EAKIN et al, 2009(EAKIN et al, , 2010aPLOTNIKOFF et al, 2012). Entretanto, por se tratar de países desenvolvidos, observa-se que o nível de instrução dos pacientes com DM superior ao que foi encontrado nesse estudo.…”
Section: Caracterização Dos Pacientes Com Diabetes Mellitus Segundo Aunclassified
See 2 more Smart Citations